Incidence of New Choroidal Neovascularization in Fellow Eyes of Patients With Age-Related Macular Degeneration Treated With Intravitreal Aflibercept or Ranibizumab - Parikh, Ravi (JAMA Ophthalmol, 2019)
IMPORTANCE: Incidence of conversion to neovascular age-related macular degeneration (nAMD) in untreated fellow eyes of patients who are treated for nAMD in 1 eye with anti–vascular endothelial growth factor agents provides important prognostic information to clinically manage patients. OBJECTIVE: To investigate the association of treatment assignment (intravitreal aflibercept vs ranibizumab) and baseline characteristics with fellow eye conversion to nAMD in the VEGF (Vascular Endothelial Growth Factor) Trap-Eye: Investigation of Efficacy and Safety in Wet AMD (VIEW) studies. DESIGN, SETTING, AND PARTICIPANTS: This post hoc analysis of the VIEW 1 and VIEW 2 studies (randomized, double-masked, active-controlled, multicenter, 96-week, phase 3 trials comparing the efficacy and safety of intravitreal aflibercept in 2457 patients with treatment-naive eyes with nAMD) analyzed a subgroup of participants treated for nAMD in 1 eye who had untreated fellow eyes without neovascularization at baseline. All participants in the VIEW studies were included in 1 of 4 groups: ranibizumab, 0.5 mg, every 4 weeks; aflibercept, 2 mg, every 4 weeks; aflibercept, 0.5 mg, every 4 weeks; or aflibercept, 2 mg, every 8 weeks after 3 injections at 4-week intervals. Data collection in the VIEW studies occurred from July 2007 to August 2011; the data analysis presented in this report took place from April 2016 to November 2018. INTERVENTIONS: Patients received no treatment in the fellow eyes unless after conversion to nAMD, when any treatment approved by heath authorities was given per the investigators’ discretion. MAIN OUTCOMES AND MEASURES: Incidence of conversion to nAMD in patients with untreated fellow eyes that had not had clinical signs of neovascularization at baseline. RESULTS: A total of 1561 participants were included in this analysis. At 96 weeks, 375 patients (24.0%) experienced cases of conversion to neovascular disease in the fellow eye, including 107 of the 399 individuals who received ranibizumab, 0.5 mg, every 4 weeks; 93 of the 387 individuals who received aflibercept, 2 mg, every 4 weeks; 84 of the 387 individuals who received aflibercept, 0.5 mg, every 4 weeks; and 91 of the 388 individuals who received aflibercept, 2 mg, every 8 weeks after 3 doses at 4-week intervals. The rates were 18.1, 16.2, 14.7, and 16.0 per 100 patient-years at risk at week 96, respectively. On multivariate analysis, fellow eye conversion was associated with increasing patient age (per 10 years) at baseline (hazard ratio [HR], 1.20 [95% CI, 1.05-1.36]), female sex (HR, 1.32 [95% CI, 1.06-1.63]), intraretinal fluid in the study eye at baseline (HR, 1.28 [95% CI, 1.02-1.61]), and increasing choroidal neovascularization lesion size (per 10 mm(2)) in the study eye at baseline (HR, 1.29 [95% CI, 1.06-1.57]). Rates of fellow eye conversion were similar with either of the treatments. CONCLUSIONS AND RELEVANCE: In this secondary analysis of randomized clinical trial data, patients with active nAMD in 1 eye appeared to have a high risk for fellow eye conversion. Such patients should be monitored closely.